Aroma-matrix interaction in food: an APCI approach - Gan, H. H. (2015)
An overview is presented of the principle, scope and major applications to date of the use of atmospheric pressure chemical ionisation mass spectrometry (APCI-MS) for monitoring the kinetics of release of flavour volatiles in real time. There are four major areas in this thesis that extend from the measurement of flavour molecular mobility in sugar solutions, to the investigation of APCI-MS as a diagnostic tool for classifying apple cultivars and predicting age of cheese. Headspace techniques are the most extensively employed techniques in food analysis to measure volatile compounds, which play a central role in the perceived quality of food. The use of APCI-MS to measure aroma headspace availability with the addition of solutes was evaluated for two sugars of differing chain lengths (fructose and fructooligosaccharide (FOS)). In vitro aroma release was investigated at equilibrium using APCI-MS. An increase in the concentration of fructose above 25 % (w /w) was shown to significantly (p < 0.05) increase the release of ethyl butyrate, ethyl acetate and benzaldehyde into the gas phase above the aqueous solutions. Proton nuclear magnetic resonance (1 H NMR) was used to investigate the nature of solvent-sugar-aroma interactions with a view to explain the differential availability of aroma volatiles in sweetened and biopolymer rich solutions. The T1 relaxation times, and diffusion coefficients, provided preliminary clues as to the interactions between water, aroma and biopolymer.